2009
DOI: 10.1002/gcc.20670
|View full text |Cite
|
Sign up to set email alerts
|

Frequent upregulation of MYC in plasma cell leukemia

Abstract: Plasma cell leukemia (PCL) is a rare form of monoclonal gammopathy, which can originate de novo or evolve from multiple myeloma (MM) as a terminal leukemic phase. Previous cytogenetic studies of PCL have reported the presence of complex karyotypes with involvement of multiple unidentified chromosomal regions. We report here the analysis of 12 PCL (10 primary and two secondary) by metaphase and FISH analysis combined with oligonucleotide array data (244 k, Agilent). Interphase-FISH results were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
59
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 47 publications
14
59
3
1
Order By: Relevance
“…4). As regards IGH@ translocations involving MAF gene, we found higher frequency (30.5%) than those reported in previous works, where incidence in pPCL was approximately 10-17% [3,4] if not absent [8], and almost identical to that reported by Chiecchio et al [6]. Finally, we found a 13% incidence of t(4;14), quite similar to an earlier report [3] but different from other studies in which it was found at higher frequency (21-25%) [4,5] or completely absent [6,8].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…4). As regards IGH@ translocations involving MAF gene, we found higher frequency (30.5%) than those reported in previous works, where incidence in pPCL was approximately 10-17% [3,4] if not absent [8], and almost identical to that reported by Chiecchio et al [6]. Finally, we found a 13% incidence of t(4;14), quite similar to an earlier report [3] but different from other studies in which it was found at higher frequency (21-25%) [4,5] or completely absent [6,8].…”
Section: Discussionsupporting
confidence: 90%
“…Herein, we identified the occurrence of IGH@ translocations in 87% of pPCL cases; such an incidence overlaps with those reported by several authors [3][4][5][6]8], confirming the widely accepted notion that IGH@ translocations are almost an ubiquitous event in PCL. However, the frequency of the different types of partner loci still remains controversial and this is probably related to the heterogeneous series investigated or geographical factors, as already suggested by other Authors [8].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations